THE EXPERIMENTAL RESEARCHES OF REINFORCED CONCRETE I-BEAM ELEMENTS WITH NORMAL CRACKS WHEN TURNING - Orlova, Olga (Academic journal Industrial Machine Building Civil Engineering, 2019)
The data of experimental researches of the rigidity of reinforced concrete I-beam elements with normal cracks at the action on them of the twisting moment have resulted in this paper. It is shown that the dependence "torque-twist angle" is almost linear. Significant nonlinear deformations appear in the last stages of loading before failure. Therefore at normative torques, it is recommended to consider the work of reinforced concrete elements of the I-beam cross-section with normal cracks linear. It is shown that the presence of longitudinal reinforcement affects the strength and rigidity of beams with normal cracks. Quite a large part of the external torque is perceived by the pin forces in the longitudinal reinforcement. The difference between the external torque and the moment of the pin forces in the armature is perceived by the upper shelf of the I-beam element. In the absence of longitudinal reinforcement, the upper shelf can collapse at loads much smaller than the destructive load of beams with longitudinal reinforcement.